Diastolic Left Ventricular Function in Relation to Circulating Metabolic Biomarkers in a General Population. Issue 3 (March 2016) - Zhang, Zhen‐Yu; Marrachelli, Vannina G.; Thijs, Lutgarde; Yang, Wen‐Yi; Wei, Fang‐Fei; Monleon, Daniel; Jacobs, Lotte; Nawrot, Tim; Verhamme, Peter; Voigt, Jens‐Uwe; Kuznetsova, Tatiana; Redón, Josep; et al.
Abstract : Background: The metabolic signature associated with subclinical diastolic left ventricular (LV) dysfunction in the population remains ill defined. Methods and Results: In 711 randomly recruited Flemish (50.8% women; mean age, 50.8 years), we assessed echocardiographic Doppler indexes of diastolic LV function in relation to 44 circulating metabolites determined by nuclear magnetic resonance spectroscopy. In multivariable‐adjusted regression analysis with Bonferroni correction of significance levels applied, peak a' decreased ( P ≤0.048) and e'/a' increased ( P ≤0.044) with circulating tyrosine, high‐density lipoprotein apolipoproteins, glucose+glutamine, and an unidentified molecule. Effect sizes expressed per 1‐SD increment in the metabolite ranged from −0.277 to −0.203 cm/s for peak a' and from +0.047 to +0.054 for e'/a'. In addition, peak a' decreased ( P ≤0.031) with glucose+2‐aminobutyrate (−0.261 cm/s) and glucose+2‐phosphoglycerate (−0.209 cm/s). In partial least square discriminant analysis (PLS‐DA), metabolites associated with normal diastolic LV function (n=538) included glucose+glutamine, glucose+2‐aminobutyrate, and glucose+2‐phosphoglycerate, whereas those siding with abnormal function encompassed 4‐aminobutyrate, 4‐hydroxybutyrate, creatinine, and phosphocholine. In receiver operating characteristics plots, adding 3 latent factors identified by PLS‐DA to prohormone brain natriuretic peptide increased ( P <0.0001) the area under the curve from 0.64 (95% CI, 0.58–0.68) to 0.73 (0.68–0.78). Conclusions: In a general population, circulating metabolites indicative of energy substrate utilization and protection against oxidative stress differentiated normal from abnormal diastolic LV function. These findings improve our understanding of the pathophysiology underlying deterioration of diastolic LV function and potentially point to new targets for prevention and treatment of this condition.